Organization of industrial control computers - Rodd, Michael Godfrey (Department of Electrical Engineering, 2016)
The efficient use of industrial control computers is recognized as an organizational problem akin to the traffic-switching problem in communications. A systematic approach to this problem is proposed, based on theory developed for the handling of telephone traffic. The application of the approach indicates that it is necessary to re-evaluate traditional hardware/software relationships. A change in these relationships is desirable, since multi-programmed computers spend too much time in handling their own organization. This situation is compounded in time-critical industrial process-control applications. It is proposed that the solution lies in the use of a flexible hardware operating system, working in close relationship with a conventional minicomputer. The unit proposed to implement this function, termed a microcontroller, makes use of the new bipolar microprocessor elements and provides a high-speed, flexible control unit, adaptable to user requirements. To retain a high degree of flexibility the microcontroller is microprogrammable. In essence, the unit executes the principal functions of a real-time operating system, acts as a pre-processor for all incoming requests, and ensures a high rate of task-switching. This system is applied to a series of configurations, each selected to demonstrate, quantitatively, the value of the technique in real applications. Comparisons are made between real-time control configurations based on the software-implemented approach and the identical configurations based on this system. The proposed strategy is shown to result in a better and more economical industrial controller. The wider implication for any aspect of organization is that "bigger" is not necessarily "better". Successful management implies effective use of facilities, rather than a proliferating structure.